How Labor Market Policies Can Combine Workers' Protection and Job Creation : A Partial Review of Some Key Issues and Policy Options - Pierre, Gaëlle; Scarpetta, Stefano (Washington, DC: World Bank, 2012)
To what extend have macro and structural reforms in many developing countries affected the labor market? Are current policy settings in the labor market adequate to cope with the current challenges of a more dynamic but also more risky economic environment? Are there examples of successful labor reforms that have combined greater adaptability with greater workers? protection? What can labor policy do when resources are scarce and informality looms large? These questions are addressed in this paper as part of an in-depth review of formal policy and institutional settings in the labor market of many developing and emerging economies. Also reported on is evidence of the effects of policy reforms on job creation and on the ability of workers to cope with shocks.